Decolonising psychotherapy. Racism and the psychoanalytic profession. Issue 4 (2nd October 2021) - Morgan, Helen
Abstract : From time-to-time concern is expressed within the psychoanalytic community that so few individuals from the black and minority ethnic communities want to train with us and join our organisations. I have come to believe that these discussions many will be familiar with are not only futile but a part of the defensive structures that serve to act against the radical change that is needed. I know individuals change. However, apart from some tinkering, our institutions do not. This paper considers the defensive structures of disavowal within ourselves and our organisations as well as the features of psychoanalytic training that produce a disabling complacency. These work against the radical changes that are required if the profession is to become one to which people of colour can feel they belong and that reflects twenty first century multicultural Britain. I offer some suggestions for ways of working against the racist assumptions behind some of our theories and our structures. The underlying conviction of the presentation is that this is a white problem which white people need to address – not only for the benefit of black colleagues but because it also does us all harm.